2018
DOI: 10.33369/jeet.2.2.93-102
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Word Formation Encountered in Medical Terms in the Jakarta Post’s Articles

Abstract: The aim of this research was to find out the types of word formation in medical terms in The Jakarta Post’s health articles. This research was designed as a descriptive qualitative research. The population of this research was all medical terms in The Jakarta Post newspaper. The sample of this research was medical terms found in seven health articles in The Jakarta Post newspaper which published from June until December 2016. Documentation was used as main instrument in this research. There were 10 types of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Coinage is a word-formation process in which new words are completely created in a language (Triwahyuni, Imranuddin, & Zahrida, 2018). The new words are usually used to name new invented objects.…”
Section: Introductionmentioning
confidence: 99%
“…Coinage is a word-formation process in which new words are completely created in a language (Triwahyuni, Imranuddin, & Zahrida, 2018). The new words are usually used to name new invented objects.…”
Section: Introductionmentioning
confidence: 99%
“…Triwahyuni et al (2018) analysed the word formation process in Medical Terms found in The Jakarta Post's Articles. The researchers found 55 derivation data among the 105 data retrieved, indicating that derivation is used in the construction of most medical terminology.…”
mentioning
confidence: 99%